2014
DOI: 10.1002/eji.201444954
|View full text |Cite
|
Sign up to set email alerts
|

Epitope‐specific CD4+, but not CD8+, T‐cell responses induced by recombinant influenza A viruses protect against Mycobacterium tuberculosis infection

Abstract: Tuberculosis remains a global health problem, in part due to failure of the currently available vaccine, BCG, to protect adults against pulmonary forms of the disease. We explored the impact of pulmonary delivery of recombinant influenza A viruses (rIAVs) on the induction of Mycobacterium tuberculosis (M. tuberculosis)-specific CD4 + and CD8 + T-cell responses and the resultant protection against M. tuberculosis infection in C57BL/6 mice. Intranasal infection with rIAVs expressing a CD4 + T-cell epitope from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 56 publications
2
34
0
1
Order By: Relevance
“…In mice, BCG is a poor stimulator of CD8 + T‐cell responses compared with M. tuberculosis and this is the rationale for the development of vaccines targeting CD8 + T‐cell expansion . However, viral and subunit vaccines that lead to strong CD8 + T‐cell responses in mice did not improve protection against M. tuberculosis infection . Both these studies, however, used the immunodominant M. tuberculosis antigen, TB10.4, and TB10.4‐specific CD8 + T cells appear unable to recognize M. tuberculosis ‐infected macrophages, which suggests that M. tuberculosis may subvert the CD8 + T‐cell responses as a virulence strategy.…”
Section: New Tb Vaccine Candidates and T‐cell Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, BCG is a poor stimulator of CD8 + T‐cell responses compared with M. tuberculosis and this is the rationale for the development of vaccines targeting CD8 + T‐cell expansion . However, viral and subunit vaccines that lead to strong CD8 + T‐cell responses in mice did not improve protection against M. tuberculosis infection . Both these studies, however, used the immunodominant M. tuberculosis antigen, TB10.4, and TB10.4‐specific CD8 + T cells appear unable to recognize M. tuberculosis ‐infected macrophages, which suggests that M. tuberculosis may subvert the CD8 + T‐cell responses as a virulence strategy.…”
Section: New Tb Vaccine Candidates and T‐cell Memorymentioning
confidence: 99%
“…38 However, viral and subunit vaccines that lead to strong CD8 + T-cell responses in mice did not improve protection against M. tuberculosis infection. 39,40 Both these studies, however, used the immunodominant M. tuberculosis antigen, TB10.4, and TB10.4-specific CD8 + T cells appear unable to recognize M. tuberculosisinfected macrophages, 41 which suggests that M. tuberculosis may subvert the CD8 + T-cell responses as a virulence strategy. Despite this, a number of TB vaccines in clinical trials are designed to elicit a strong CD8 + T-cell response ( Table 1).…”
Section: New Tb Vaccine Candidates and T-cell Memorymentioning
confidence: 99%
“…[17][18][19] We have previously shown that pulmonary immunization of mice with a viral TB vaccine, recombinant influenza A virus (rIAV) expressing the p25 CD4 + T-cell immunodominant epitope of M. tuberculosis Ag85B (PR8.p25), induced strong p25-specific CD4 + Tcell responses in the lungs that were protective against M. tuberculosis challenge. 20 In this study, we have investigated whether pulmonary immunization of mice with rIAVs expressing this p25 epitope induces M. tuberculosis-specific CD4 + T cells in the lung with the tissue location, phenotype, and transcriptional characteristics of T RMs , and if these lung-resident T cells are protective against M. tuberculosis challenge in the absence of circulating memory T cells.…”
Section: Introductionmentioning
confidence: 99%
“…CD8 T cell responses increase later during infection often with a kinetic that is associated with increasing bacterial burden. Their role in protective immunity remain unresolved and recent data suggest that even very high numbers of vaccine promoted CD8 T cells specific for protective antigens fail to influence Mtb growth [20, 21]. …”
Section: Tb: Infection Immunity and Antigensmentioning
confidence: 99%